Інвестиційні аспекти нормативно-правового забезпечення виробничо-комерційної діяльності продовольчих корпорацій - Чеботарьов, Є.В. (Економіка промисловості, 2012)
Опрацьовуються підходи до нормативно-правового забезпечення виробничо-комерційної діяльності продовольчих корпорації як передумови вдосконалення їхньої інвестиційної діяльності. Запропоновано критеріальні ознаки визначення поняття «продовольчі корпорації» та висунуто пропозиції стосовно пільгового оподаткування вертикально-інтегрованих формувань у продовольчій сфері. Ключові слова: продовольча сфера, продовольчі корпорації, нормативно-правове забезпечення, інвестиції, виробничо-комерційна діяльність. Проработаны подходы к нормативно-правовому обеспечению производственно-коммерческой деятельности продовольственных корпораций как условию усовершенствования их инвестиционной деятельности. Предложены критериальные признаки определения понятия «продовольственные корпорации» и выдвинуты предложения относительно льготного налогообложения вертикально-интегрированных формирований в продовольственной сфере. Ключевые слова: продовольственная сфера, продовольственные корпорации, нормативно-правовое обеспечение, инвестиции, производственно-коммерческая деятельность. Aggravation of the contemporary global food crisis causes studying of the food industry of Ukraine. Of particular importance is the analysis of the functioning of national food corporations: they not only significantly determine the prospects of the food sector and the national economy as a whole, but are beginning to appear as the important actors in the international division of labor. The article is based on the author’s preliminary analysis of the evolution of integration processes in the food sector in the domestic science of 60-80 years of the twentieth century, the study of this problem at the stage of market reforms, review of food policy of the European Union under the Common Agricultural Policy and empirical material on managing food corporations of Ukraine. The paper offers the approaches to regulatory support of the industrial and commercial activities as a precondition for food corporations to improve their investment. On the grounds of generalization of the current economic law and theoretical and methodological provisions, the economists suggested the criteria for the definition of "food corporation." In order to optimize the investment process of food corporations based on the concept of balance of incentives and constraints, the proposals for tax incentives in priority sectors of the food industry of Ukraine and classification of product innovation in the food sector are provided. Implementation of these proposals will provide the analysis and assessment of food corporations’; status restraint of the outflow of domestic capital from the country, identification of a base regulatory support to the industrial and commercial process of food corporations oriented to encourage their investment and innovation. Keywords: food sector, food corporations, legal support, investment, industrial and commercial activities.